Le Temple, le Portugal et l’Orient latin - Philippe Josserand (Medievalista)
In Portugal, the Temple has long been thought as having no connections with the Latin East and it still remains so with few exceptions. Even among specialists, it is still admitted that the Portuguese province of the order, by benefiting from a gradual autonomy, would have known a definitive estrangement from the Holy Land at the end of the thirteenth century. To challenge this preconceived idea, it is used in this paper an unpublished document kept in the Archivo de la Corona de Aragón which, in 1282, implicates Lourenço Martins, lieutenant of the provincial master of Portugal, in a Mediterranean transport from Barcelona to Acre. He would travel with four brothers, forty-five to fifty animals, accompanied by the squires and their corresponding bales and supplies. At the time, such shipments were not uncommon. They formed part of a tradition of contacts between Portugal and the East which remains largely unknown. The Templars were certainly not the only agents of this relationship, but they played a crucial role, which undermines the national character so readily lent to their order in the land of Fernando Pessoa and of an ever-lively Templarism.